Postulat de la monnaie et théorie de la valeur chez Marx - Nicolas Piluso (Revue de la Régulation)
The paper attempts to reevaluate the criticism of Carlo Benetti about the marxian theory of money. If indeed it is impossible to deduce the existence of money from value theory, we propose to postulate money within the theory of value. This type of assumption is fundamentally different from the keynesian postulate of money which leads to reject the theory of value and distribution. This proposition of a “marxian postulate of money” has the advantage of preserving the teachings brought by the marxian analysis of the monetary economy.